Lineage most lethal - Perkins, S. C. (Stephanie C.) (Perkins, S. C. (Stephanie C.). Ancestry detective mystery., 2020)
"Lineage Most Lethal is the captivating second mystery in S.C. Perkins' Ancestry Detective series, in which Texas genealogist Lucy Lancaster grapples with murders in both the past and present. It's the week before New Year's Eve and genealogist Lucy Lancaster is mixing work and play quite nicely at the boutique Sutton Hotel in Austin, Texas. After two months of research she's finalizing her presentation for hotel heiress Pippa Sutton, her latest client. Lucy has just arrived back at the hotel after a day of research when a strange man comes staggering toward her. She barely has time to notice his weak, sweaty appearance and broken tooth before he presses a classic Montblanc pen into her hand, whispers, "keep them safe," and collapses at her feet, dead. Lucy only knows one person who might be able to explain the significance of the pen: her grandpa, who is a collector. But Grandpa has an odd reaction to the sight of the pen, and Lucy can't help but feel that it might have something to do with his experiences during World War II. When Lucy becomes convinced that her hotel room has been searched and that there's more to the pen-and her grandpa-than meets the eye, she begins to draw connections from the present-day deaths and suspicious behaviors to a group of spies in World War II. Secret codes, old grievances, and traitors seem to hide behind every corner, and as Lucy begins to connect the dots someone seems determined to make sure the Lancaster line ends once and for all"--